(untitled) (Journal of Global Accounting, 2023)
This study examines risk as a determinant of dividend policy of quoted commercial banks in Nigeria. Specifically, the study intends to ascertain the extent of relationship between debt security and dividend payout ratio of quoted commercial banks in Nigeria. Furthermore, it intends to evaluate the extent to which equity security relates with dividend payout ratio of quoted commercial banks in Nigeria. The ex-post facto research design was adopted while a total of 13 quoted commercial banks actively trading in the floor of Nigeria Exchange Group constituted the sample size of this study for the years 2008 – 2021 using purposive sampling technique. Inferential and descriptive statistic using correlation analysis was employed. The data analysis reveals that equity securities and debt securities are significantly positively related with dividend payout ratio. Conclusively, equity securities and debt securities are the key determinant factor of dividend policy of quoted commercial banks in Nigeria. It is recommended that, since there is positive relationship between equity securities and dividend policy, deposit money banks should pay more attention to retain earnings than to give out profit as dividend.